Deserving a Just Pension: A Factorial Survey Approach*. (18th October 2018) - Castillo, Juan Carlos; Olivos, Francisco; Azar, Ariel
Abstract : Objective: This study analyzes which characteristics of pension recipients are taken into account when evaluating the fairness of pensions. Furthermore, it identifies some respondents' characteristics and preferences that could be related to the justice evaluation of different pension amounts. Methods: A factorial survey was designed to simultaneously analyze the association of respondents' and recipients' characteristics with the pensions' justice evaluation. Results: Findings indicate that although there is a consensual demand for larger pensions, it is still believed that pensions should be allocated primarily based on individual achievement. Conclusions: Although in general, larger pensions are on average considered as more just, the justice criteria rely heavily on individual achievement over redistributive considerations, showing willingness to accept very low pensions for those considered not deserving them.